(3GdCMcGe aj GdfLhes - (3CHh SYjO Hf efUhQ Hf Ydj HfOGQ GdOGeZGfjs ((3GdNGJhfjI (B_ (3eOjfI GdSdGe s)
(3ChdgG (B:s
:(3eLehY CbGhjd GdMceGA GdefLejf GdbOeGA efge hGdeMOKjf ai CMcGe JMGhjd Sfi GdehGdjO , hgh HYdGeGJ CSGejge gQeS (B(5) (3, hGdjS GdEScfOQGfi s
(3BNQgG (B:s
(3hcPdc EPG GfJgi Sge SYGOI GdSfI Edi JQHjY GdSYhO hGdcjfhfI eYgG ai HjhJgG , hGfJgi GdTgQ Edi SeJ GdSYhO jOd Ydi GdNjQ Je GdcJGH HMeO Gddg s
(3Cdag eDdag SfI (B507 (3g`s
(3cJHJ Hbde ajg edGeM GdNW GdaGQSis
(3cJHJ HQSe NRGfI CHj GdMSf Ydi Hf fVjQGdOjf GdWhSis
(3HChdgG bGFeI HeUGOQ GdcJGH s
(3HgG fXGe GdJYbjHI s
(3GdfSNI ebGHdI cJHJ YfhGfGJgG HMHQ eNGda s
Keywords: (3Gdadcs